PEMBERDAYAAAN MASYARAKAT KAMPUNG ARSOPURA, DISTRIK SKANTO, KABUPATEN KEEROM, PAPUA MELALUI PEMBUATAN SAOS TOMAT SAGU - Tri Gunaedi; Euniche R.P.F. Ramandey (JURNAL PENGABDIAN PAPUA, 2021)
The implementation of science and technology activities on the application of making sago tomato sauce aims to provide skill to the villagers Arsopura on how to make a good sago tomato sauce healthy. The skill of production tomato sago sauce was given by the demonstration of resource persons and repetition by the participants with five variations of sago tomato sauce composition. Assesment relating to sago tomato sauce products that have been produced are done by organoleptic testing. In other hand was determined pH, and viscosity of sago tomato sauce processing. Organoleptic test deals with the fondness of color, odor, aroma and taste with very very like, very likes, likes,rather likes, dislikes and very dislike criteria of the five variations of tomato sago sauce produced. Test results obtained sago tomato sago with a mixture of 100 and 150 grams of curly chili is very favorable to the respondents. It is recommended to produce sago tomato sauce should there be a mixture of enough curly chili to have the taste in accordance with the consumer like.Key words: sago, tomato and sauce